A review of the evolution of the Cocos Malays dwellings in Australia - Osri, Nurul Ain; Hj Mohd Ariffin, Noor Aziah (Asia Pacific Institute of Advanced Research, 2016)
This paper studies the unique anthropology of the Cocos Malays of Cocos (Keeling) Island in Australia. The focus of the study is on the evolution and transformation of their dwelling architecture and culture. Cocos Island is an isolated coral atoll located in the vast Indian Ocean and it became a home for the small community of Cocos Malays. Cocos Malays is a group of people from various ethnicities who were brought by a British merchant as slaves when he decided to inhabit and settle on the island in the 1820s. The slaves were a combination of people, mostly of Malay origin with the majority coming from Banjarmasin, Indonesia. These people later became assimilated into what is known today as the Cocos Malays. Starting by being slaves to the British and later as Australian subjects, this paper traces their history through the transformation of their dwelling culture until the present time. The dwellings, apart from serving the function of basic needs for the human being also acts as a place for them to experience their sense of belonging, culture and worth of a people displaced by circumstances beyond their control. Through archival research and present observations, the paper in progress elucidates the transformation of the architectural practices of the Cocos Malays’ dwelling culture.